Dynamic Lung Functions in Underweight Gujarati Indian Adolescents Boys - Hasmukh D Shah; Wasim A Shaikh; Divyangi Patel; S K Singh (Medsci Publications, 2012)
Background: Underweight due to poor nutrition is the serious problem in our country. Undernourishment is associated so many health problem in children and adolescents. The objective of the study was to study the association of underweight on dynamic lung functions in Gujarati Indian adolescents. Methodology: A cross sectional study was conducted on 85 Gujarati Indian adolescents boys of 17-21 years age group. The nutritional status of the participants was assessed by measuring BMI and they were grouped into normal weight and underweight boys. Total body fat % and fat mass were measured by Omron Body Fat Monitor HBF-302. Dynamic lung functions (FEV1, FEV6, FEV1/FEV6 and PEFR) were recorded, using Piko-6 and Wright's Peak flow meter. Results: FEV1 (P <0.01), FEV6 (P <0.01) and PEFR (P <0.01) were found to be significantly lower in the underweight boys in comparison to the normal weight boys. BMI showed a significant positive correlation with dynamic lung functions. Amongst underweight boys body mass index and fat mass index were directly associated with dynamic lung functions. Conclusion: We may conclude that nutritional status plays a major role in dynamic lung functions in Gujarati Indian adolescents.